Ionospheric correction of ALOS‐2 full‐aperture ScanSAR interferometric data for surface deformation measurement in Beijing. Issue 19 (3rd July 2019) - Ning, Jiaqi; Wang, Robert; Wang, Jili; Zhang, Bowen; Zhao, Shuang
Abstract : Ionospheric disturbance is one of the most serious factors that limit the accuracy of deformation measurement of interferometric synthetic aperture radar (InSAR) especially for spaceborne SAR systems in low frequency such as L‐band. Especially in imaging modes with a large coverage, ScanSAR mode for example, ionospheric disturbance phase screen almost submerges other useful geographical information. In this study, two ALOS‐2 (L‐band) full‐aperture ScanSAR images (October 2015 and October 2016) are used to study ground deformation in Beijing from 2015 to 2016. The split range‐spectrum technique is adopted to extract ionospheric distortion. The authors splice the differential interferograms of adjacent subswaths by resampling them to perform the overall ionospheric extraction. Also non‐local filtering is used to improve the coherence of interferograms. Spatial deformation distribution that was obtained by differential interferometric synthetic aperture radar (D‐InSAR) technique using the two ALOS‐2 ScanSAR images is highly consistent with the result obtained by persistent scatterer interferometric synthetic aperture radar (PS‐InSAR) technique using Sentinel Tops mode images (October 2015–February 2017). The comparison results show the effectiveness of the ionospheric distortion extraction method used in this study. Moreover, the spatial distribution is also highly consistent with the results before 2014, which means that the deformation trend in Beijing continues.